2022
DOI: 10.1146/annurev-pathmechdis-032521-102529
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Inflammasome in Liver Disease

Abstract: The involvement of inflammasomes in the proinflammatory response observed in chronic liver diseases, such as alcohol-associated liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD), is widely recognized. Although there are different types of inflammasomes, most studies to date have given attention to NLRP3 (nucleotide-binding oligomerization domain-like receptor family, pyrin domain containing 3) in the pathogenesis of ALD, NAFLD/nonalcoholic steatohepatitis, and fibrosis. Canonical inflammasomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 120 publications
1
95
0
Order By: Relevance
“…Increasing studies have shown that cold exposure can result in liver damage [ 21 , 22 ]. In addition, the involvement of pyroptosis, inflammasomes and oxidative stress in the pro-inflammatory response is observed in many liver diseases, such as metabolic-associated fatty liver disease, nonalcoholic fatty liver disease and alcohol-associated liver disease [ 23 , 24 ]. However, very few studies have revealed pyroptosis’s underlying mechanisms of cold stress in liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have shown that cold exposure can result in liver damage [ 21 , 22 ]. In addition, the involvement of pyroptosis, inflammasomes and oxidative stress in the pro-inflammatory response is observed in many liver diseases, such as metabolic-associated fatty liver disease, nonalcoholic fatty liver disease and alcohol-associated liver disease [ 23 , 24 ]. However, very few studies have revealed pyroptosis’s underlying mechanisms of cold stress in liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that dhBBR reduces inflammation via an NOD-like receptor pyrin domain-containing 3 (NLRP3) inflammasome-related mechanism, which likely reduces the release of caspase-1,apoptosis-associated speck-like protein (ASC) and IL-1β to inhibit pyroptotic cell death, which is a form of programmed cell death that occurs in liver fibrosis. ( Xu et al, 2021a ; de Carvalho Ribeiro and Szabo, 2021 ). dhBBR may even have better anti-sclerotic effects than BBR.…”
Section: Anti-fibrosis Effects Of Berberine In the Livermentioning
confidence: 99%
“…In the liver, pathogen‐associated molecular patterns (PAMPs, such as gut‐derived LPS) and DAMPs (e.g. ATP) released from damaged hepatocytes in response to ethanol induce a local sterile inflammatory response that involves activation of inflammasomes especially NLRP3 (de Carvalho Ribeiro & Szabo, 2022; Szabo, 2017). NLRP3 activation requires a two‐step process.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, consisting mainly of neutrophilic infiltrates, is one of the main characteristics of ASH development (Bertola, 2020). Current studies on the inflammatory response in ASH have mostly (de Carvalho Ribeiro & Szabo, 2022;Szabo, 2017). NLRP3 activation requires a two-step process.…”
Section: Discussionmentioning
confidence: 99%